Care for the world : Laudato si' and Catholic social thought in an era of climate crisis / edited by Frank Pasquale. - Pasquale, Frank (Law and Christianity., 2018)
Convening leading scholars to reflect on the practical and philosophical implications of religious values, this volume is an accessible introduction to Catholic social thought on contemporary affairs. Its gracefully written chapters cover three themes - direct environmental policy implications of Laudato Si', philosophical alternatives to dominant policy discourse, and renewed political economy based on robust conceptions of human flourishing. Care for the World offers learned reflections on what it would mean to express an ethic of compassion in an era of climate crises.